Verifying reference intervals for coagulation tests by using stored data - ÇİLİNGİRTÜRK, AHMET METE (TAYLOR & FRANCIS LTD, 2011)
Objective: The purpose of the study was to verify the reference intervals for prothrombin time (PT) and activated partial thromboplastin time (APTT), using stored data of ambulatory pre-op subjects with exclusion of certain clinics, according to age and sex. Materials and Methods: Results of test requests (13,600 PT and 14,083 APTT) of subjects aged 15-80 made from outpatient clinics of surgical departments before surgical interventions in 2008 were retrieved from the electronic medical record. Thromborel S and Actin (Dade Behring, Germany) were used on the Sysmex(R) CA-1500 coagulation analyzer. Extreme values were determined by using Horn's algorithm after Box-Cox transformation, and the upper and lower reference limits were determined as the 2.5th and 97.5th percentiles of the cleaned data. Results: The values outside the interval of PT data 10.5-17.0 seconds and the interval of APTT data 20.6-35.8 seconds were excluded from the analysis. There were significant differences among age subsets of PT measurements (p < 0.0001) and of APTT measurements (p < 0.0001). Accordingly, the data were tested for gender differences and a significant difference was found in PT (p = 0.002). APPT results did not differ statistically between men and women. Conclusion: Although we found values different from the limits stated in the kit insert, it would be better to confirm our findings with the direct method, especially in APTT for patients under the age of 40 and over the age of 59, and also for sex differences in PT.
Keywords: Blood coagulation tests; data storage; hematology; reference ranges; statistical data analysis; PARTIAL THROMBOPLASTIN TIME; PATIENT DATA; VENOUS THROMBOEMBOLISM; HEMOSTATIC SYSTEM; REFERENCE LIMITS; REFERENCE VALUES; POPULATION; THERAPY; ENZYMES; RISK